2016
DOI: 10.1515/pcssr-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Does Sport Event Involvement Influence Brand Recognition of Official Sponsors and Ambush Marketers?

Abstract: The main aim of the study is to verify how event involvement in the UEFA Euro 2012 influenced the recognition of both sponsors’ and ambushers’ brands. Computer-Assisted Personal Interviews were conducted on a representative sample of the Polish society (N = 1,000). On the basis of five groups of consumers regarding involvement in the event, authors examined brand recognition, using Top of Mind Awareness (TOMA) tests of official sponsors and ambushers.The highest TOMA rate was observed in the group of heavy vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Some scholars discuss the effect of event involvement on ambush marketing. Piątkowska and Gocłowska (2016) showed the relative effect of involvement in an event on recognizing sponsors, while Wolfsteiner et al (2015b) found that event involvement did not affect ambush marketer misidentification. A recent study illustrated that fans who watched the games during the 2016 FIFA football championship were more forgiving of ambushers in beer and gambling industries compared with industries in general; and in the same research, women were not as indulgent of ambush marketing as were men (Burton and Chadwick, 2019).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Some scholars discuss the effect of event involvement on ambush marketing. Piątkowska and Gocłowska (2016) showed the relative effect of involvement in an event on recognizing sponsors, while Wolfsteiner et al (2015b) found that event involvement did not affect ambush marketer misidentification. A recent study illustrated that fans who watched the games during the 2016 FIFA football championship were more forgiving of ambushers in beer and gambling industries compared with industries in general; and in the same research, women were not as indulgent of ambush marketing as were men (Burton and Chadwick, 2019).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A maioria dessas medições no patrocínio ocorre via auto-relato em ambientes pouco controlados (BACHLEDA; FAKHAR; ELOUAZZANI, 2015; CLARK; CORNWELL; PRUITT, 2009;DE HOUWER, 2003;KO et al, 2008;KUDO et al, 2015;NGAN;PRENDERGAST;TSANG, 2011;PIĄTKOWSKA;GOCŁOWSKA, 2016;SPAIS;JOHNSTON, 2014;WALLISER, 2003) e, dessa maneira, muitos autores postulam sobre a importância do uso de estudos experimentais para melhorar a compreensão do processamento do patrocínio e em técnicas que consigam captar níveis atitudinais genuínos e espontâneos (ALONSO DOS SANTOS et al, 2016a;MADRIGAL, 2000;NGAN;PRENDERGAST;TSANG, 2011;PARGANAS et al, 2017;THOMPSON, 2000).…”
Section: Introductionunclassified